2020
DOI: 10.2147/cmar.s243172
|View full text |Cite
|
Sign up to set email alerts
|

<p>Impact of Nutritional Indices on the Survival Outcomes of Patients with Colorectal Cancer</p>

Abstract: Background: The effect of preoperative nutritional status on the survival of patients with colorectal cancer is still unknown. The purpose of our study was to examine the impact of the prognostic nutritional index (PNI), prealbumin (PAB) and the albumin to globulin ratio (AGR) on survival outcomes in patients with colon and rectal cancer. Methods: Between January 2012 and December 2013, 361 patients with colorectal cancer who underwent curative surgery in the survey and various clinical and haematological para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Higher levels of PNI have been associated with favorable prognosis in lung [ 24 , 25 ], colorectal [ 30 ], breast [ 26 ], prostate [ 29 ], and cervical [ 21 ] cancers. Nonetheless, few reports have investigated the role of PNI in HNC, so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher levels of PNI have been associated with favorable prognosis in lung [ 24 , 25 ], colorectal [ 30 ], breast [ 26 ], prostate [ 29 ], and cervical [ 21 ] cancers. Nonetheless, few reports have investigated the role of PNI in HNC, so far.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PNI has also been recognized as an accurate parameter reflecting nutritional and inflammation status [ 19 ]. In the last few years, PNI has been extensively investigated as predictor of poor outcome in several types of cancer [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], including HNC [ 31 , 32 , 33 , 34 ]. Although a number of studies have evaluated PNI in relation to treatment toxicity [ 35 , 36 , 37 , 38 ], only few ones focused on HNC [ 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that PNI is associated with the prognosis of oesophageal ( 32 ), gastric ( 33 ), and colorectal ( 34 ) cancer patients; PNI has also been used to predict oncological outcomes in HCC patients receiving immunotherapy ( 35 ) or hepatectomy ( 36 ). However, the predictive value of PNI in HCC patients receiving immunotherapy combined with targeted therapy remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…PNI includes the measures of serum albumin and peripheral blood lymphocytes. Albumin, which constitutes up to 60% of plasma, is produced in the liver, reflects the nutritional status, is regulated by inflammatory cytokines and may play crucial roles in tumorigenesis and cancer progression ( 25 ). Serum albumin is positively correlated with the prognosis of colorectal cancer ( 26 ).…”
Section: Discussionmentioning
confidence: 99%